Mapping Research Trends on Agricultural Resilience in Scholarly Publications (2012–2024) - Loso Judijanto; Dyah Ayu Suryaningrum (West Science Agro, 2026)
Agricultural resilience has emerged as an increasingly important research domain in response to global challenges related to climate change, food security, environmental degradation, and sustainable agricultural development. This study aims to map the development, intellectual structure, collaboration patterns, and emerging themes of agricultural resilience research published between 2012 and 2024. A bibliometric approach was employed using scholarly publications indexed in Scopus as the primary data source. The collected bibliographic data were analyzed using VOSviewer to examine publication trends, co-authorship networks, institutional collaboration, country collaboration, citation structures, keyword co-occurrence, overlay visualization, and density mapping. The findings indicate that agricultural resilience research has experienced substantial growth and developed into a multidisciplinary field integrating environmental science, agricultural systems, sustainability studies, and technological innovation. Collaboration analysis identified the United States, China, and India as dominant contributors and central actors in global research networks, while institutional and author analyses revealed the existence of several interconnected scholarly communities. Citation analysis showed that the field is strongly influenced by foundational works on planetary boundaries, ecosystem resilience, climate-smart agriculture, biodiversity conservation, and sustainable development. Keyword mapping demonstrated that major themes include climate change, agriculture, food security, sustainable agriculture, crop resilience, and ecosystem management, with recent developments increasingly emphasizing precision agriculture, machine learning, physiological stress, and adaptive agricultural technologies.